The 90-kDa heat-shock protein (Hsp90)-binding immunophilin FKBP51 is a mitochondrial protein that translocates to the nucleus to protect cells against oxidative stress - Gallo, L.I. (2011)
Confocal microscopy images revealed that the tetratricopeptide repeat motif (TPR) domain immunophilin FKBP51 shows colocalization with the specific mitochondrial marker Mito-Tracker. Signal specificity was tested with different antibodies and by FKBP51 knockdown. This unexpected subcellular localization of FKBP51 was confirmed by colocalization studies with other mitochondrial proteins, biochemical fractionation, and electron microscopy imaging. Interestingly, FKBP51 forms complexes in mitochondria with the glucocorticoid receptor and the Hsp90/Hsp70-based chaperone heterocomplex. Although Hsp90 inhibitors favor FKBP51 translocation from mitochondria to the nucleus in a reversible manner, TPR domain-deficient mutants of FKBP51 are constitutively nuclear and fully excluded from mitochondria, suggesting that a functional TPR domain is required for its mitochondrial localization. FKBP51 overexpression protects cells against oxidative stress, whereas FKBP51 knockdown makes them more sensitive to injury. In summary, this is the first demonstration that FKBP51 is a major mitochondrial factor that undergoes nuclear-mitochondrial shuttling, an observation that may be related to antiapoptotic mechanisms triggered during the stress response. © 2011 by The American Society for Biochemistry and Molecular Biology, Inc.